2007
DOI: 10.1016/j.jacc.2007.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Aortic Valve Replacement for Severe Aortic Stenosis in High-Risk Patients Using the Second- and Current Third-Generation Self-Expanding CoreValve Prosthesis

Abstract: Treatment of severe aortic valve stenosis in high-risk patients with percutaneous implantation of the CoreValve prosthesis is feasible and associated with a lower mortality rate than predicted by risk algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
387
0
27

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 879 publications
(426 citation statements)
references
References 19 publications
12
387
0
27
Order By: Relevance
“…The devices used int hi sst ud yan dth eT A V Rp r o c e d ur eh av ebe e np r eviously described (12)(13)(14).T h eb a l l o o n -e x p a n d a b l e valve used in this trial (Edwards SAPIEN XT; Edwards Lifesciences, Irvine, California) is a cylindrical cobalt-chromium stent into which 3 leaflets made of bovine pericardium are mounted, whereas the self- STUDY ENDPOINTS. The pre-specified primary endpoint of the CHOICE trial was "device success," as defined by the first Valve Academic Research Consortium (VARC) consensus document (15) and has been previously reported (12).A l lp a t i e n t sw e r e followed-up for at least 1 year and had clinical visits and echocardiographic evaluations at 6 months and 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…The devices used int hi sst ud yan dth eT A V Rp r o c e d ur eh av ebe e np r eviously described (12)(13)(14).T h eb a l l o o n -e x p a n d a b l e valve used in this trial (Edwards SAPIEN XT; Edwards Lifesciences, Irvine, California) is a cylindrical cobalt-chromium stent into which 3 leaflets made of bovine pericardium are mounted, whereas the self- STUDY ENDPOINTS. The pre-specified primary endpoint of the CHOICE trial was "device success," as defined by the first Valve Academic Research Consortium (VARC) consensus document (15) and has been previously reported (12).A l lp a t i e n t sw e r e followed-up for at least 1 year and had clinical visits and echocardiographic evaluations at 6 months and 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…Atualmente cerca de 25 mil pacientes já foram tratados com esse dispositivo no mundo e a experiência acumulada com o emprego dessas biopróteses em pacientes com contraindicação ou com alto risco cirúrgico indica que os resultados são bastante promissores. [7][8][9][10][11][12] Recentemente, iniciou-se a experiência com o sistema CoreValve TM no Brasil, 13,14 que motivou a criação de um registro nacional para aferir os resultados do implante percutâneo de biopróteses aórticas em nosso meio.…”
Section: Key-wordsunclassified
“…Nesse grupo, a abordagem por cateter tem elevada chance de sucesso e pode oferecer mortalidade inferior àquela esperada com o tratamento cirúrgico. 7,[10][11][12]15 O risco cirúrgico pode ser estimado por diversos escores. Os mais empregados são o EuroSCORE 16 e o STS 17 , validados em centros europeus e americanos, respectivamente.…”
Section: Seleção De Pacientesunclassified
“…A self-expanding prosthetic valve can be deployed percutaneously via a retrograde approach in approximately 84-93% of patients. When successfully implanted, it increases aortic valve area, reduces transvalvular gradients, and improves New York Heart Association functional class, but major adverse cardiac events occurred in as many as 32% of patients at short term follow-up, which included death in 20% [10][11][12]. The largest trial to date which included 86 patients reported a procedural mortality of 6%, a 30-day mortality of 12%, and a cumulative incidence of death, stroke, and myocardial infarction of 22% [12].…”
Section: Discussionmentioning
confidence: 99%
“…When successfully implanted, it increases aortic valve area, reduces transvalvular gradients, and improves New York Heart Association functional class, but major adverse cardiac events occurred in as many as 32% of patients at short term follow-up, which included death in 20% [10][11][12]. The largest trial to date which included 86 patients reported a procedural mortality of 6%, a 30-day mortality of 12%, and a cumulative incidence of death, stroke, and myocardial infarction of 22% [12]. Percutaneous AVR is also limited by bleeding (24%) and paravalular leakage (48%) and might be less successful in the setting of a bicuspid aortic valve [13].…”
Section: Discussionmentioning
confidence: 99%